Clinical Outcomes and Microbiological Characteristics of Sequence Type 11 Klebsiella pneumoniae Infection - Yang, Ping; Wu, Zhenchao; Liu, Chao; Zheng, Jiajia; Wu, Nan; Wu, Zhangli; Yi, Juan; Lu, Ming; Shen, Ning (Frontiers in Medicine, 2022)
Background Sequence type 11 (ST11) Klebsiella pneumoniae (Kp), is commonly prevalent in China, typically encountered in KPC-producing isolates. This study aimed to evaluate the clinical outcomes and microbiological features of ST11 Kp infections. Methods A retrospective cohort study was conducted in Peking University Third Hospital from January 2017 to March 2021. Clinical data were collected from medical records. Antimicrobial susceptibility testing and string test were performed. Whole-genome sequencing was used to analyze the capsular serotypes, virulence-associated genes, and multi-locus sequence typing. Risk of all-caused death in ST11 Kp infected patients were compared to non-ST11 Kp infected patients. Results Among 139 patients infected with Kp, 49 ST11-Kp (35.3%) were isolated. Charlson comorbidity index in the ST11 group was higher, compared with the non-ST11 group (3.94±1.59 versus 2.41±1.54, P=0.001). A greater number of ST11 Kp infected patients experienced ICU admission (46.9% versus 16.7%, P<0.001) and mechanical ventilation (28.6% versus 10.0%, P=0.005). All ST11 presented with multidrug-resistant (MDR) phenotype, and twenty-nine (59.2%) hypervirulent Kp (hvKp) emerged. Twenty-four ST11 strains presented with hypermucoviscosity. The presence of capsule-associated genes K47 and K64 was frequent in ST11 Kp strains (P<0.001). The key virulence-associated genes rmpA, rmpA2, iucA, iroB, peg344 respectively accounted for 26.5%, 42.9%, 59.2%, 0%, 26.5% in the ST11 group. Twenty-one ST11 isolates harbored the combination of iucA+rmpA2. The 30-day mortality and Sequential organ failure assessment (SOFA) score were significantly higher in ST11 Kp infected patients than non-ST11 group (P<0.01). ST11 Kp infection appeared to be independent risk factor for mortality of ST11 Kp infected patients. Conclusions High prevalence of ST11 clone was found in hospital, which accounted for more antimicrobial resistance and exhibited great molecularly inferred virulence. Patients with ST11 infection had increased tendency of 30-day mortality and SOFA score. ST11 Kp infection was the independent risk factor for mortality, suggesting that enhanced surveillance and management are essential.